Dismantling the Role of Family Environment in Supporting Students’ English Learning: A Case Study at SMA Al-faqih Muqaddam Kubu Raya. - Nizar Rahmadi; Alvina Yolanda; Fikri Irawan; Muhammad Yassin; Muhammad Sood (CAKRAWALA LINGUISTA, 2026)
This study aims to explore the role of the family environment in supporting students’ English learning at SMA Alfaqih Muqaddam Kubu Raya and to identify the forms of parental support and challenges faced in the process. The research utilized a qualitative descriptive method with a case study design to gain in-depth insights into the familial context. Data were collected through semi-structured interviews with five students, three parents, and one English teacher, complemented by field observations and documentation. The data analysis technique employed was thematic analysis, which involved data reduction and categorization to identify patterns of familial involvement. The results of the study indicate that the family environment plays a crucial role in enhancing students’ motivation and confidence. Parental support was implemented through activities such as reminding children to study, providing learning facilities like providing wifi at home and Android TV for accessing video and English learning website for learning English, and encouraging daily practice at home. In addition, students also admitted that they were encouraged to join English course and their parents pay for it.the parents buy them book and dictionaries for studying English. Meanwhile, as the time constrain the parents could not accompany the student in studying as not all parents have English proficiency and proper English skill to give direct intervention in teaching English. In conclusion, consistent support and effective cooperation between parents and teachers are essential factors in improving students' English learning achievement.